Can Immune Tolerance Be Re-established in Neuromyelitis Optica? - Loda, Eileah; Arellano, Gabriel; Perez-Giraldo, Gina; Miller, Stephen D.; Balabanov, Roumen (Frontiers in Neurology, 2021)
Neuromyelitis optica (NMO) is a chronic inflammatory disease of the central nervous system that primarily affects the optic nerves and spinal cord of patients, and in some instances their brainstem, diencephalon or cerebrum as spectrum disorders (NMOSD). Clinical and basic science knowledge of NMO has dramatically increased over the last two decades and it has changed the perception of the disease as being inevitably disabling or fatal. Nonetheless, there is still no cure for NMO and all the disease-modifying therapies (DMTs) are only partially effective. Furthermore, DMTs are not disease- or antigen-specific and alter all immune responses including those protective against infections and cancer and are often associated with significant adverse reactions. In this review, we discuss the pathogenic mechanisms of NMO as they pertain to its DMTs and immune tolerance. We also examine novel research therapeutic strategies focused on induction of antigen-specific immune tolerance by administrating tolerogenic immune-modifying nanoparticles (TIMP). Development and implementation of immune tolerance-based therapies in NMO is likely to be an important step towards improving the treatment outcomes of the disease. The antigen-specificity of these therapies will likely ameliorate the disease safely and effectively, and will also eliminate the clinical challenges associated with chronic immunosuppressive therapies.